The Influence of Industry-Based Curriculum Management and Student Character on the Quality of Graduates at SMK Negeri 3 Tondano - Norry Etsiko Rompas; Romi J. Mongdong; Zoya F. Sumampouw (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the impact of industry-based curriculum management and student character on graduate quality at SMK Negeri 3 Tondano, using a quantitative approach with correlational methods and regression analysis. The sample comprised 42 graduates from the Light Vehicle Engineering program (academic years 2023/2024 and 2024/2025), selected through total sampling. Data were collected via validated questionnaires and analyzed using simple and multiple linear regression. The findings indicate that industry-based curriculum management has a positive and significant effect on graduate quality (R²=0.644, p<0.05), student character also has a positive and highly significant effect (R²=0.609, p<0.01), and both factors together significantly influence graduate quality (F-count=20.977 > F-table=3.238), contributing 88.2% to graduate quality. This study highlights the dominant role of student character in determining graduate quality, followed by the effectiveness of curriculum management aligned with industry needs, providing strategic recommendations for enhancing graduate competitiveness in vocational education. Keywords: Industry-based curriculum, student character, graduate quality, vocational education, SMK